2020
DOI: 10.5194/bg-2020-46
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stable isotopic composition of top consumers in Arctic cryoconite holes: revealing different position in supraglacial trophic network

Abstract: Abstract. Cryoconite holes are ecosystems on the glacier surface characterized by dynamic nature and truncated food webs. It is acknowledged that cryoconite holes play an important role being biodiversity hot-spots and factories for organic matter on glaciers. The most common cryoconite apex consumers are the cosmopolitan invertebrates – tardigrades and rotifers. Several studies have highlighted the relevance of cryoconite tardigrades and rotifers to cryoconite holes’ ecosystem functioning. However, due to the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…Zawierucha et al [ 17 ] and Buda et al [ 22 ] did not find any clear trophic relationship between primary producers and grazers in cryoconite holes on the margin of the Greenland Ice Sheet (Russel Glacier) or on a maritime Antarctic glacier, respectively. In contrast, Jaromerska et al [ 28 ], using stable isotope ratios, revealed different use of food sources by tardigrades and rotifers in High Arctic cryoconite holes, although the food sources were unidentified. These studies were not able to present robust and clear relationships between grazers, their food sources and other biota.…”
Section: Introductionmentioning
confidence: 95%
“…Zawierucha et al [ 17 ] and Buda et al [ 22 ] did not find any clear trophic relationship between primary producers and grazers in cryoconite holes on the margin of the Greenland Ice Sheet (Russel Glacier) or on a maritime Antarctic glacier, respectively. In contrast, Jaromerska et al [ 28 ], using stable isotope ratios, revealed different use of food sources by tardigrades and rotifers in High Arctic cryoconite holes, although the food sources were unidentified. These studies were not able to present robust and clear relationships between grazers, their food sources and other biota.…”
Section: Introductionmentioning
confidence: 95%
“…There are two potential scenarios which might explain this unrecognized pattern in cryoconite holes. In comparison with areas of snow algae blooming, cryoconite holes host very diverse biota and rich organic matter, thus diet of invertebrates might be complex which may constrain understanding of food preferences 45 . Secondly, dynamic nature of cryoconite holes in Arctic and alpine regions like rapid ablation, inter-hole watersediment mixing and stochastic weather events disturb or sometimes destroy habitats on surface of ice like cryoconite holes 30,46 , hence in dynamic habitats ndings of any ecological relations are problematic.…”
Section: Discussionmentioning
confidence: 99%